2003
DOI: 10.1046/j.1365-313x.2003.016010.x
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional acetyl‐CoA carboxylase 1 is essential for very long chain fatty acid elongation and embryo development in Arabidopsis

Abstract: SummaryAcetyl-CoA carboxylase (ACCase) catalyses the carboxylation of acetyl-CoA, forming malonyl-CoA, which is used in the plastid for fatty acid synthesis and in the cytosol in various biosynthetic pathways including fatty acid elongation. In Arabidopsis thaliana, ACC1 and ACC2, two genes located in a tandem repeat within a 25-kbp genomic region near the centromere of chromosome 1, encode two multifunctional ACCase isoforms. Both genes, ACC1 and ACC2, appear to be ubiquitously expressed, but little is known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
187
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(197 citation statements)
references
References 52 publications
7
187
0
1
Order By: Relevance
“…Because all known mutants in flavonoid synthesis have normal embryos, the absence of VLCFA and their derivatives must be the cause of embryo arrest in acc1 plants (Baud et al, 2003). Interestingly, we detected PvACCase gene promoter-directed GUS activity in the Arabidopsis embryo (Fig.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Because all known mutants in flavonoid synthesis have normal embryos, the absence of VLCFA and their derivatives must be the cause of embryo arrest in acc1 plants (Baud et al, 2003). Interestingly, we detected PvACCase gene promoter-directed GUS activity in the Arabidopsis embryo (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…In this context, Baud et al (2003) showed that acc1 mutants displayed defects in embryo development and in VLCFA synthesis. Mutants in the GURKE gene, which encodes ACC1, exhibit embryo defects and its cotyledons are absent or highly reduced (Kajiwara et al, 2004).…”
mentioning
confidence: 99%
“…In lower eukaryotes, cytosolic ACC, which is the homolog to animal ACC1, is essential to the viability and development of yeast and the embryos of Arabidopsis (24,33). A null mutation in the acc1 gene of Arabidopsis resulted in embryo lethality, and it was suggested that this lethality is caused by the lack of synthesis of very long-chain fatty acids (33).…”
Section: Discussionmentioning
confidence: 99%
“…Selective herbicides kill grasses such as wheat by specific binding and inhibition of the enzymatic activity in plastids (19), and possibly also in mitochondria (9). Arabidopsis mutants in which the cytosolic ACC gene is disrupted are embryo-lethal and deposit triacylglycerides lacking VLCFAs (20). Finally, all current evidence (8) implicates the ACC reaction as an important regulatory step, controlling metabolite flow during plant development and in response to stress.…”
Section: Discussionmentioning
confidence: 99%